Plant community response to Artemisia rothrockii (sagebrush) encroachment and removal along an arid elevational gradient. (27th August 2018) - Kopp, Christopher W.; Cleland, Elsa E.
Abstract: Questions: Shrub expansion into alpine ecosystems worldwide raises important questions regarding the influence of shrub encroachment on alpine species diversity. The stress gradient hypothesis (SGH) predicts interactions will be competitive when resources are plentiful and the environment is benign, but that facilitative interactions will dominate when conditions are stressful. We asked how Artemisia rothrockii (sagebrush) encroachment in an arid mountain range is affecting alpine plant species there and how the plant community responds to the experimental removal of sagebrush at three sites along an elevational gradient. Location: The White Mountains, California, USA (37°30′N, 118°10′W). Methods: A shrub removal experiment was established at three elevations (2, 900, 3, 100 and 3, 750 m) to evaluate how sagebrush interacts with alpine and sub‐alpine plant communities. Results: The study sites experienced a strong drought over the 4 yrs of the experiment and plant cover declined overall. However, in the sagebrush removal treatment, cover of co‐occurring species increased at both the high‐elevation and low‐elevation sites, with no differences observed at the mid‐elevation site. Conclusions: We observed the greatest inhibitory effects of sagebrush at high and low elevations, where plants experience the largest temperature and moisture stress, respectively, and no evidence of facilitation anywhere along the elevational gradient. These results demonstrate that while sagebrush has important influences on herbaceous species composition in the White Mountains, they are inconsistent with the classic predictions of the SGH. Abstract : Shrub expansion into alpine ecosystems raises important questions regarding their impact on biodiversity. The stress gradient hypothesis predicts interactions will be competitive when resources are plentiful, but facilitative when conditions are stressful. Along an elevational gradient of contrasting temperature and moisture stress, we observed the greatest inhibitory effects of sagebrush at high and low elevations, but no evidence of facilitation.